Komunikasi Kelompok Pada Komunitas Cah-Cah Kolektif Dalam Kebersamaan Bermusik - Agung Dwi Suprayogo; Tony S Soekrani (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
Humans cannot achieve what they want with themselves and must communicate in their lives. As human social beings need other people and need groups or communities to interact with each other. Various groups can also be formed by having different characteristics and goals. One example is the collective music community. The collective group that carries the do it yourself (DIY) slogan. Where in this group refused the intervention of the owners of capital in the event of the gigs they held, where they only relied on cohesiveness in the formation of their own networks in carrying out their group activities. This study aims to determine the function of Group Communication on Collective Cah-Community in Music Togetherness. The functions described are in the form of Social Relations Functions, Educational Functions and Information Sharing, Persuasion Functions, Problem Solving Functions and Decision Making, and Therapy Functions. This research was conducted using a qualitative approach, and used in-depth interviews and observations as data collection tools. The research subject refers to the problem under study, namely the members of the Collective Cah-cah community. The results of the study were based on interviews and observations conducted by researchers on the Collective Cah-Cah community that group members used the function of group communication functions for the continuity of their groups, such as making communities a place to form social relations, as a place for information that is important to the community, making communities as a means of finding solutions and making decisions, changing the mindset of members, and improving the nature and behavior with the encouragement of the community it self.